Assessment of salinity intrusion in an aquifer system in the southwest region of Bangladesh - Adhikary, Sajal Kumar; Babel, Mukand Singh; Gupta, Ashim Das; Clemente, Roberto S.; Perret, Sylvain Roger; Netherlands Ministry for Development Cooperation (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Groundwater resources development and management on a regional basis is an important requirement for a developing country like Bangladesh which often experiences the lack of surface water resources of adequate quality to meet the rising freshwater demand. The coastal belt surface water systems in the southwest region of the country have already been affected by saline water intrusion from the sea. Groundwater systems may be affected by salinity intrusion from the sea and affected surface water systems through dynamic interaction mechanisms. In addition, further groundwater development and sea level changes could aggravate the situation. Finding a solution to such a problem requires thorough investigation and analysis of the overall system in an integrated manner. Taking this into account, the present study is an attempt to investigate the salinity intrusion phenomena into the groundwater system in the southwest region of Bangladesh. An integrated river-aquifer modeling approach is used for analyzing the groundwater flow characteristics and dynamic interaction of the rivers and the underlying aquifers. A three(S1(Bdimensional groundwater simulation model, MOD FLOW, is applied for this purpose. An area of 16,985 km2 covering almost entire southwest region of Bangladesh is considered for the present case study. Stratigraphic analysis of sub-surface lithology is done to define the aquifer system in the study area. The calibrated flow model satisfactorily simulates the flow characteristics of the regional groundwater system and dynamic interactions between rivers and aquifers. A three-dimensional numerical mass transport simulation model, MT3DMS, is applied to develop the saltwater intrusion model. The model is then applied to assess salinity intrusion, by advection process, into the groundwater systems for existing mean sea level and sea level rise condition in 2030. For both cases, the model results show that the saline front lies close to the sea boundary located far away from the study area border. The simulation results of dynamic interaction showed that salinity intrusion from surface water bodies, in the form of recharge water, is the predominant factor affecting groundwater system rather than the intrusion directly from the sea side. The study conclusively proves that in the integrated river-aquifer systems in coastal region, the interactions between the rivers and the underlying aquifer systems have significant influence on the flow and salinity intrusion into the overall systems
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2008
Keywords: Water salinization -- Evaluation -- Bangladesh